MANAJEMEN KEPEMIMPINAN DI SDN 173115 SITOMPUL - Evi Novalin Bako; Jimmy Marthin Yunus Situmorang; Roy Dedi Ansarika; Luckas Patiolo Purba (ELT (English Language Teaching Prima Journal), 2023)
The purpose of this research is to identify and analyze the leadership style of the principal of SD Negeri 173115 Sitompul. The method was used in this research is descriptive qualitative research method. This research was used descriptive qualitative because the researcher described what kind of situationhappened in public schools, especially in terms ofthe leadership style applied by the principal at SD Negeri 173115 Sitompul .Interviews, obeservation and field notes was used in this research. The data were cooleected and interpredted based on the types of leadership style. From the research, it was found that the pricipal of SD Negeri 173115 Sitompul applied a servant leadership type, in which the implementation of this leadership is carried out by prioritizing a moral and familial approach.